Socioeconomic status and motivation in endurance sports: insights from long-distance running - Akbaş, Anna; Żebrowska, Aleksandra; Malchrowicz-Mośko, Ewa; Stempień, Jakub; Bezuglov, Eduard; Górka-Chowaniec, Agnieszka; Waśkiewicz, Zbigniew (Frontiers in Psychology, 2025)
IntroductionEndurance running is a popular activity with varying motivations, yet the influence of socioeconomic status (SES) on these motivations has not been thoroughly explored. This study investigates how SES (income, education, vocational status) shapes the motivations of three groups of runners: recreational runners (RRs), marathoners (MAs), and ultramarathoners (Us) in Poland.MethodsA large-scale online survey (N = 1,539) was conducted between January and March 2008, capturing participants’ demographic characteristics, running experience, and motivation.ResultsThe results reveal differences in motivational priorities across groups. Us were more motivated by achievement and self-esteem, while RRs prioritized social affiliation, and marathoners showed a balance between the two. However, the reported effect sizes (η2 = 0.01) suggest that while differences exist, they are small in practical significance. Higher-SES individuals focused on achievement-related goals, while lower-SES individuals emphasized health benefits and social connection. The analysis also found that higher-SES participants were more likely to complete marathons and ultramarathons, with financial stability and professional access playing a key role.DiscussionNevertheless, ultramarathon participation appeared to depend more on intrinsic motivation than financial resources. These findings underline the complex interplay between SES, personality, and experience, emphasizing the need for tailored strategies to support diverse runners. Further research may explore the broader psychological and cultural factors influencing running motivations.